2005
DOI: 10.1002/jca.20059
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange as a nephrological procedure: A single-center experience

Abstract: In the United States, therapeutic plasma exchange (TPE) is both performed and requested by a wide range of services, often on an empiric basis (before a diagnosis is established). Whether empiric therapy is beneficial has not been established. Patients were identified from an electronic procedure log that included those patients who received plasmapheresis at Walter Reed Army Medical Center from 1996 to 2003. The clinical indications, referring service, and outcomes (including deaths) that occurred were tabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
3
17
1
Order By: Relevance
“…There was a severe complication rate of 22%, and a mortality rate of 11%. The underlying diagnosis may have had an effect on morbidity and mortality; however, 39% of patients had a diagnosis for which TPE was not standard and acceptable treatment [17]. In a study limited to TPE treatment for TTP (a disease with a very high mortality rate if untreated), there were 73 major complications in 206 consecutively treated patients, and 5 patients (2.4% of the total) died of complications that may have been related to TPE [18].…”
Section: Discussionmentioning
confidence: 92%
“…There was a severe complication rate of 22%, and a mortality rate of 11%. The underlying diagnosis may have had an effect on morbidity and mortality; however, 39% of patients had a diagnosis for which TPE was not standard and acceptable treatment [17]. In a study limited to TPE treatment for TTP (a disease with a very high mortality rate if untreated), there were 73 major complications in 206 consecutively treated patients, and 5 patients (2.4% of the total) died of complications that may have been related to TPE [18].…”
Section: Discussionmentioning
confidence: 92%
“…Most large registries report a relatively low incidence (5 to 12%) of complications associated with TA procedures, with the exception of two, relatively small, single center series [21][22][23][24][25][26][27][28][29][30] (Figure 2). Most adverse events are categorized as Grade 1: Mild (no intervention required, 1.5%) or Grade II: Moderate (intervention required but treatment completed, 2.5%) (Table III).…”
Section: Clinical Adverse Events During Therapeutic Apheresismentioning
confidence: 93%
“…Hemolytic anemia has been reported in cases, in which albumin was improperly diluted with sterile water, instead of saline. Hypotension has been reported when albumin is rendered hypo-oncotic (3.3%) when diluted with saline, and may explain the high incidence of total adverse events in one of the single-center series [30]. Both can be avoided by using 5% albumin.…”
Section: Clinical Adverse Events During Therapeutic Apheresismentioning
confidence: 95%
“…The coagulation profile is further modified by TPE‐related factors such as procedure frequency and duration, procedural plasma volume, and replacement fluid . Despite TPE's effects on coagulation, studies have consistently demonstrated that TPE‐associated bleeding risk is low …”
mentioning
confidence: 99%